Odontogenic MSC Heterogeneity: Challenges and Opportunities for Regenerative Medicine - Chen, Yuan; Zhang, Zhaoyichun; Yang, Xiaoxue; Liu, Anqi; Liu, Shiyu; Feng, Jianying; Xuan, Kun (Frontiers in Physiology, 2022)
Cellular heterogeneity refers to the genetic and phenotypic differences among cells, reflecting their various fate choices including viability, proliferative state, self-renewal probability, and differentiation lineage options. In recent years, research on the heterogeneity of mesenchymal stem cell has made some progress. Odontogenic mesenchymal stem cells share the characteristics of mesenchymal stem cells, namely easy accessibility, low immunogenicity and high stemness. In addition, they also exhibit the characteristics of vasculogenesis and neurogenesis, making them to be attractive in tissue engineering and regenerative medicine. However, the usage of mesenchymal stem cell subgroups differs in different diseases. Furthermore, because of the heterogeneity of odontogenic mesenchymal stem cells, their application on tissue regeneration and disease management is under restriction. Heterogeneity of odontogenic mesenchymal stem cells is urge to be summarized, we thus reviewed odontogenic mesenchymal stem cells and their specific subpopulations, in order to provide indications for further research on the stem cell regenerative therapy.